Evaluation of a Sunscreen Product Compared with Reference Standards P3, P5 and P8 in Outdoor Conditions: a Randomized, Double-Blinded, Intra-individual Study in Healthy Subjects - Granger, Corinne; Petkar, Gitanjali; Hosenally, Muzzammil; Bustos, Javier; Trullàs, Carles; Passeron, Thierry; Krutmann, Jean (Dermatology and therapy, 2022)
Introduction The shortcomings of standardized sunscreen testing have been discussed in recent years, noting differences between how sunscreens perform in indoor clinical (in vivo) laboratory testing compared with real-life conditions. We previously developed an outdoor clinical method for ranking sunscreens by performance level. We used this method to test the performance of a new broad-spectrum sunscreen against International Organization for Standardization (ISO) reference products P3, P5 and P8. Methods Sixty-five healthy volunteers with individual typology angle (ITA) ≥ 28° (light to intermediate skin colour) participated in an outdoor study in Mauritius. Test areas were marked on their backs, which were treated with the different products: one commercially available broad-spectrum sun protection factor (SPF) 50 sunscreen [investigational product (IP)] and the three reference products P3 (SPF 15), P5 (SPF 30) and P8 (SPF 50+) from ISO norm 24444:2019 for SPF testing. The test areas were exposed for 2–3 h, depending on the baseline skin colour. They were also compared with an unprotected positive control area and a non-exposed negative control area. Clinical and colorimetry assessment of erythema and pigmentation were performed at 24 h and 8 days, respectively. Results Overall, according to this outdoor clinical testing method, the sunscreens’ efficacy was ranked in an appropriate order given their established SPF levels, with higher SPFs giving greater protection against erythema and pigmentation. Between the different levels of SPF, the differences were statistically significant, for both clinical and colorimetry assessments. The new broad-spectrum SPF 50 IP performed similarly to the SPF 50+ (P8) reference product. Even the highest SPF products, SPF 50 and SPF 50+, had some instances of photoprotection failure. Conclusion These findings confirm the feasibility of this outdoor clinical testing method in ranking sunscreens and provide further evidence, in addition to standardized SPF and UVA protection factor (UVAPF) testing, on how this new broad-spectrum SPF 50 sunscreen performs in extreme outdoor solar exposure: in line with reference product P8 (SPF 50+). Trial Registration No. ISRCTN95394014.